1992
DOI: 10.1093/ajcp/97.4.559
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Commercial Enzyme Immunoassays Compared to Immunofluorescence and Double Diffusion for Autoantibodies Associated with Autoimmune Diseases

Abstract: A commercially available enzyme immunoassay system for detecting autoantibodies to double-stranded DNA, deoxyribonucleoprotein, Smith, ribonuclearprotein, Sjögren's syndrome-associated antigens A and B, and scleroderma-associated antigen 70 was compared to the conventional immunofluorescence assay for double-stranded DNA and double diffusion assays for extractable nuclear antigens. There was excellent correlation between methods, but it appears that the enzyme immunoassays are more sensitive. Based on the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Few studies have compared the sensitivity and specificity of the newer methods with standard methods. [3][4][5] Most reports do not include clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have compared the sensitivity and specificity of the newer methods with standard methods. [3][4][5] Most reports do not include clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…An assay should be accurate and produce the same result as other assays on all serum samples to enable comparison between diVerent centres. An international reference preparation (IRP) for anti- [33][34][35][36] CLIF is less likely than ELISA to detect low aYnity anti-dsDNA of uncertain clinical relevance, [37][38][39][40][41][42] especially if IgG specific conjugates are used. Local validation of each assay is essential to ensure adequate diagnostic performance.…”
Section: Antinuclear Antibodies (Anas)mentioning
confidence: 99%
“…Other investigators who have compared monospecific ENA antibody EIA results and ID results also reported a small percentage of discordant EIA-positive/ID-negative result sets (8,(10)(11)(12). Because some patients with discordant results exhibited clinical characteristics consistent with connective tissue diseases (10,12) it has been suggested that EIA may be more sensitive than ID, and should replace ID as the gold standard for ENA antibody detection.…”
Section: Discussionmentioning
confidence: 99%
“…Because some patients with discordant results exhibited clinical characteristics consistent with connective tissue diseases (10,12) it has been suggested that EIA may be more sensitive than ID, and should replace ID as the gold standard for ENA antibody detection. Unfortunately, this issue could not be addressed in this study, since all specimens were referred to MRL from other laboratories, and complete clinical information was not available.…”
Section: Discussionmentioning
confidence: 99%